DNA amplification fingerprinting using 10 x polymerase chain reaction buffer with ammonium sulfate for human identification - Baransel, A; Dulger, HE; Tokdemir, M (Saudi Med J, 2004)
Objective: The polymerase chain reaction (PCR) based DNA amplification fingerprinting (DAF) or randomly amplified polymorphic DNA (RAPD) is based on a strategy using a single arbitrary oligonucleotide primer to generate anonymous amplification of genomic DNA. On this basic strategy, in this study, we aimed to test individual differences and usefulness of 2 basic primers (5'-CGCGCCGG-3' and 5'-TGCCGAGCTG-3') and examined whether there is a positive effect on results of 10 x PCR buffer with ammonium sulfate. Methods: A new approach in DNA fingerprinting, 10 x PCR buffer with ammonium sulfate, is presented in the study. Primers with single 8 and 10 nucleotides in length and 2 different PCR buffers with or without ammonium sulfate were used to identify 135 volunteers with no blood relationship. This study was carried out at the Pharmacology Laboratory, University of Gaziantep, School of Medicine, Turkey between 1999 and 2000. Results: An average of 10 major bands representing 500-1500 base pair (bp) in length was determined as amplified DNA products on standard agarose gels for these volunteers. The use of ammonium sulfate in 10 x PCR buffers has increased to 92% success ratio of individual difference obtained from the 8 nucleotides primer. Conclusions: With this study, more reliable results can be obtained by using ammonium Sulfate in 10 x PCR buffers.
Keywords: Arbitrary Oligonucleotide Primers; Hla-Dq-Alpha; Forensic Specimens; Genetic-Markers; Vntr Analysis; Reaction Pcr; Population; Humth01; Locus; Polymorphisms